Palestinian diaspora entrepreneurship - a driving force in the knowledge economy / Mervat Hatem N. Shahin - Shahin, Mervat Hatem N. (2012)
National economies are becoming more knowledge based-economies where productivity and growth have become more dependent on knowledge. In view of this rising globalised knowledge economy, trans-national migrants are playing an increasing role contributing to demographic changes and answering to the competition amongst nations for skilled knowledge nomads. Emigrated intellectual, skilled, and technological people are an invaluable resource for the development of their respective home countries. Their contributions to economic development are substantial through platforms of the knowledge economy, and via knowledge networks. Entrepreneurs, be they local or Diaspora, have become a key element of economic development, success, and sustainability. Entrepreneurship is presently the most effective method for bridging the gap between science and marketplace, creating new enterprise, and bringing new products and services to the market. So, the purpose of the study is to bridge or channel Palestinian’s Diaspora entrepreneurs to be a part of the development process in Palestine via entrepreneurship. The challenge that is facing Palestinian Diaspora is how to bridge the Palestinian Diaspora entrepreneurs that are distributed around the world with the development inside Palestine through entrepreneurship. This study discusses entrepreneurial networks interactions positioning entrepreneurs among Palestinian Diaspora as a global asset in driving innovative capabilities. This study aims at building a framework for stronger relationships between Palestinian Diaspora and development in Palestine based on a strong supporting platform of science, engineering, technology & innovation (SET&I). The framework for the linkages positions the entrepreneurs among Palestinian Diaspora as the central driving force for successful implementation of the study. The study identifies and evaluates causes of mobility of the Palestinian Diaspora (push-pull factors), and evaluates entrepreneurial characteristics of Palestinian Diaspora by identifying their capacity and capability. Also, this study discusses the entrepreneurial Palestinian Diaspora and proposes a mechanism and a strategy that enable the Palestinian Diaspora to be a part of the development in Palestine. This exploratory study employed both quantitative (a survey) and qualitative (interviews) methodologies in order to cover the empirical gap. A snowball sampling was used as a strategy in the distribution process. The quantitative approach was by distributing a survey among Palestinian Diaspora worldwide, manually, or electronically, by creating a specific website for this purpose. The results identified the push-pull factors between Palestinian Diaspora, and show that Palestinian Diaspora is skilled people with entrepreneurial characteristics. The results also show high awareness among Palestinian Diaspora to contribute with the development process through different mechanisms. A model consists of six main themes was tailored and examined its validity and reliability, and the correlation between its components, and the correlation between the model and the independent variables (push-pull, and re-pull factors), to enable entrepreneurs among Palestinian Diaspora to play a strong role in the development of Palestine.